Specific features of acute stroke in the Russian Federation and in the People’s Republic of China (according to the data of some big stroke units) - S. S. Yu; E. V. Melnikova; Zhou Jing; A. A. Shmonin; A. G. Shumeeva; E. A. Bondarevna; M. A. Karachevtseva; V. I. Dorofeyev (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The study focuses on comparison and analysis of the work of big stroke units in the Russian Federation and the People’s Republic of China specialized in the medical care for patients with acute stroke. 522 patients were surveyed in Russia’s and China’s regional stroke units. In the Russian Federation, patients being treated in the «City Hospital No.26» (SaintPetersburg) took part in the study. In China patients of the First Affiliated Hospital of the Chongqing Medical University, Central Hospital Jiang jin, Regional People’s Hospital Yubei district, Regional People’s Hospital Bishan (Chongqing Province). The analysis of differences was performed by the following parameters: personality traits, age, gender, level of education, income, health insurance category, profession, employment, professional activities over the last year, place of residence of the patient, features of the stroke, time during the first symptoms of stroke to hospitalization, kinds of medical services, the main risk factors and value of prevention before stroke.